(untitled) (Olhar de Professor, 2024)
This article focuses on discussions found in some of the volumes (Cadernos) of the Literacy and Lettering Collection (Coleção Alfabetização e Letramento), from the Center for Literacy, Reading and Writing - Ceale/UFMG. The research adopted a qualitative and documentary approach with emphasis on exploratory and informative reading (Salvador, 1978). Theoretical support was sought from authors such as Freire (1967,1987), Geraldi (1985), Mortatti (2020), Smolka (1999), who, in Brazil, have based a dialogical and discursive perspective on literacy. It can be concluded that the volumes in the Literacy and Lettering Collection cover important theoretical and practical discussions in the field of literacy. Regarding the concepts of "child" and "teaching work", the documents in the Collection are aligned with the dialogical and discursive perspective. On the other hand, they mobilize the category of "literacy", which does not find support in the discussions developed according to a dialogical and discursive perspective of literacy.